Epidemiological and etiological characteristics of community-acquired pneumonia in conscripts in the modern period. Comparative evaluation of the effectiveness of pneumococcal vaccines - P. V. Kulikov; S. D. Zhogolev; R. M. Aminev; K. D. Zhogolev; A. A. Kuzin; S. R. Rubova; A. N. Gorenchuk; E. A. Mikheeva (Журнал инфектологии)
The purpose of the study is to analyze morbidity and to determine etiology of community-acquired pneumonia of conscripts, to examine the epidemiological effectiveness of pneumococcal conjugate and non-conjugate polysaccharide vaccines for the prevention of community-acquired pneumonia in soldiers.Materials and methods. The incidence of communityacquired pneumonia of conscripts in the period from 2008 to 2017 was examined. PCR diagnosis of samples sputum and smears from the pharynx of 694 patients with pneumonia of conscripts was carried out to detect fragments of DNA/RNA of 14 different pathogens. Epidemiologic efficacy of conjugated and non-conjugated pneumococcal vaccine was studied in groups from a total population of 1727 soldiers.Results. It is established that over the past 8 years, the incidence of community-acquired pneumonia of military conscripts decreased by 2.7 times. However, the level of morbidity achieved in 2017 (25.7 ‰) is still very high compared to the incidence of contract soldiers (5.3 ‰) and the population (4.2 ‰).When determining the etiology of pneumonias in military conscripts by means of PCR diagnosis, the prevalence of S. pneumoniae and adenoviruses was established, the genetic material of which was detected in 56.3% and 35.9% of the examined samples, respectively. 56.1% of pneumonia had mixed, mainly viral-bacterial etiology.Among those who were vaccinated with pneumococcal conjugate vaccine, the incidence of community-acquired pneumonia was 4.5 times lower in the 5 – month follow – up period than in the comparison group (p < 0.001) (effectiveness was 77.7%), and among those who were vaccinated with non-conjugate polysaccharide vaccines it was 2.8 times lower (p < 0.001) (effectiveness was 64.3%).It was found that the use of pneumococcal conjugate vaccine in military teams formed a collective immunity that prevents the circulation of pneumococci and the development of diseases not only in vaccinated persons, but also in unvaccinated persons.Conclusion. Both types of pneumococcal vaccines – conjugate, first used in the military, and usually used non-conjugate polysaccharide vaccine, have shown high epidemiological effectiveness in the prevention of community-acquired pneumonia and can equally be recommended for vaccination of recruits a month before the call to military service and of young soldiers, not vaccinated before the call.